问题 解答题
能简算的要简算.
3
4
×
6
13
÷
9
26
4
9
÷(
1
3
+
1
3
5
9
×7+
5
9
×11
7
12
-
5
18
)×36
[1-(
1
4
+
3
8
)]÷
1
4
4
25
×99+
4
25
3
5
×
2
3
+
2
5
÷1
1
2
答案

(1)

3
4
×
6
13
÷
9
26

=

3
4
×
6
13
×
26
9

=

9
26
×
26
9

=1;

(2)

4
9
÷(
1
3
+
1
3
),

=

4
9
÷
2
3

=

2
3

(3)

5
9
×7+
5
9
×11,

=

5
9
×(7+11),

=

5
9
×18,

=10;

(4)(

7
12
-
5
18
)×36,

=

7
12
×36-
5
18
×36,

=21-10,

=11;

(5)[1-(

1
4
+
3
8
)]÷
1
4

=(1-

5
8
)÷
1
4

=

3
8
×4,

=

3
2

(6)

4
25
×99+
4
25

=

4
25
×(99+1),

=

4
25
×100,

=16;

(7)

3
5
×
2
3
+
2
5
÷1
1
2

=

3
5
×
2
3
+
2
5
×
2
3

=(

3
5
+
2
5
)×
2
3

=1×

2
3

=

2
3

填空题
单项选择题